Preventing Deep Vein Thrombosis After Stroke: Strategies and Recommendations - Kappelle, L. Jaap (Current Science Inc., 2011)
The risk of deep vein thrombosis (DVT) after stroke is increased in patients with restricted mobility, a previous history of DVT, dehydration, or comorbidities such as malignant diseases or clotting disorders. Patients with an increased risk of DVT should receive prophylactic treatment. To reduce the chance of DVT, patients should be mobilized as soon as possible and should be kept well hydrated. Anti-embolism stockings cannot be recommended, because they have been demonstrated not useful for preventing DVT or pulmonary embolism in patients with stroke, and they are associated with a significantly increased risk of skin breaks. The usefulness of intermittent pneumatic compression is currently under study in a randomized clinical trial. Treatment with subcutaneously administered low-dose unfractionated heparin is preferred to unfractionated heparin and may be considered in patients with ischemic stroke if the risk of DVT is estimated to be higher than the risk of hemorrhagic complications. Aspirin may also be effective for patients with ischemic stroke who have contraindications to anticoagulants, although direct comparisons with anticoagulants are not available. In patients with intracerebral hemorrhage, low-dose subcutaneous low-molecular-weight heparin is probably safe after documentation of cessation of active bleeding, and may be considered on an individual basis after 3 to 4 days from stroke onset.